2018
DOI: 10.1002/cam4.1491
|View full text |Cite
|
Sign up to set email alerts
|

miR‐541 suppresses proliferation and invasion of squamous cell lung carcinoma cell lines via directly targeting high‐mobility group AT‐hook 2

Abstract: An increasing number of studies have demonstrated that micro‐ribonucleic acids (miRNAs) are important tumor suppressors during carcinogenesis. However, the function of miRNA‐541 (miR‐541) in malignancies, especially lung cancer, has not been widely reported. In this study, miR‐541 expression was significantly decreased in squamous cell lung carcinoma (SCLC) cancerous tissue and SCLC cell lines. To analyze miR‐541 function in SCLC, we overexpressed miR‐541 in SCLC cell lines (SK‐MES‐1 and H226). According to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The important roles of HMGA2 and its downstream genes in tumor progression have been demonstrated in earlier studies 4,5 . Our previous studies have also identified HMGA2 as an oncogene in squamous cell lung carcinoma 6,20 . In this study, using RNA sequencing, we identified specific expression patterns of HMGA2-related circRNAs in the human lung adenocarcinoma cell line A549.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The important roles of HMGA2 and its downstream genes in tumor progression have been demonstrated in earlier studies 4,5 . Our previous studies have also identified HMGA2 as an oncogene in squamous cell lung carcinoma 6,20 . In this study, using RNA sequencing, we identified specific expression patterns of HMGA2-related circRNAs in the human lung adenocarcinoma cell line A549.…”
Section: Discussionmentioning
confidence: 84%
“…The important roles of HMGA2 and its downstream genes in tumor progression have been demonstrated in previous studies 4,5 . One of our previous studies showed that HMGA2 enhanced cell proliferation and invasion in squamous cell lung cancer 6 . To date, the regulatory effects of HMGA2 on protein-coding oncogenes have been demonstrated by multiple studies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Upregulation of eca‐miR‐493b and eca‐miR‐541 was associated with advanced tumour stage (ESA) in ES tumours and might therefore also be of prognostic significance. Interestingly, these miRNAs possess rather tumour‐suppressive functions in diverse human cancers where they are often downregulated . If upregulation of eca‐miR‐493b and eca‐miR‐541 drives oncogenesis in ES and whether inhibition of these two miRNAs could possibly stop ES disease progression, needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-541 acts as a tumor suppressor in some cancers including lung cancer and pancreatic cancer. Overexpression of miR-541 has been reported to reverse cancer progression through suppression proliferation and invasion of cancer cells [34][35][36]. We discovered that recovery of miR-541 expression in gemcitabine-resistant PCa cells resensitized them to gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%